Directory of North American Egyptologists - University of Arizona (1988)
[Dt.:] Seit 1988 erstellt die Universität von Arizona ein Verzeichnis der nordamerikanischen ÄgyptologInnen mit Position innerhalb der Ägyptologie und Kontaktdaten. - [Engl.:] Since 1988 the UAEE has published the Directory of North American Egyptologists which provides the names and contact data for professional Egyptologists and current doctoral students in North America, as well as listing current and recent doctoral dissertations in Egyptology.